Regulatory T Cells Control Immune Responses through Their Non-Redundant Tissue Specific Features - Lehtimäki, Sari; Lahesmaa, Riitta (Frontiers in Immunology, 2013)
Regulatory T cells (Treg) are needed to control immune responses and to maintain immune homeostasis. Most potent regulators are Foxp3 expressing CD4+ T cells which can be roughly divided in to two main groups, natural Treg cells (nTreg) developing in the thymus and induced or adaptive Treg cells (iTreg) developing in the periphery from naïve, conventional T cells. Both nTreg cells and iTreg cells have their own, nonredundant roles in the immune system, with nTreg cells mainly maintaining tolerance towards self-structures and iTreg developing in response to externally delivered antigens or commensal microbes. In addition, Treg cells acquire tissue specific features and are adapted to function in the tissue they reside. This review will focus on some specific features of Treg cells in different compartments of the body.